2019
DOI: 10.1108/wje-09-2018-0329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fused deposition modelling process parameters on mechanical properties of 3D printed parts

Abstract: Purpose This paper aims to explore the effect of bed temperature, primary layer thickness and infill pattern (rectilinear, honeycomb, triangular) on the mechanical properties of tensile strength and bending strength of 3D printed parts. Design/methodology/approach Samples in accordance to various ASTM standards were printed by fused deposition modelling (FDM) method by varying the various input paramaters such as bed temperature, primary layer thickness and infill pattern (rectilinear, honeycomb, triangular)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…Similar results were reported by Chadha, et al (2019) [ 69 ] who studied how grid, triangular and honeycomb infill patterns perform under the flexural and tensile loadings. It was found that the triangular pattern has the highest strength followed by the grid and finally by honeycomb patterns under both bending and tension.…”
Section: Influence Of Process Parameters On the Strength Of Fdm Partssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were reported by Chadha, et al (2019) [ 69 ] who studied how grid, triangular and honeycomb infill patterns perform under the flexural and tensile loadings. It was found that the triangular pattern has the highest strength followed by the grid and finally by honeycomb patterns under both bending and tension.…”
Section: Influence Of Process Parameters On the Strength Of Fdm Partssupporting
confidence: 88%
“…Alayoldi, et al (2020) [68] investigated the effect of the infill pattern on the compressive strength of the part. It was found that triangular, grid and hexagonal infilled parts resulted in similar ultimate tensile strength (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72), while the quarter cubic infill exhibited a significantly lower strength of 27 MPa. It was also found that the grid pattern had the highest tensile strength due to its special layer arrangement in which the infill layers are crisscrossed one above the other as shown in Figure 5.…”
Section: Effect Of Infill Patternsmentioning
confidence: 99%
“…AM provides extensive advantages of manufacturing complex geometries, improved performance, lesser wastage of raw materials and simplified fabrication process. [17][18][19] The research is continuously carried out on employing stem cell-based therapies to reduce the diseases. AM aims to replace and generate organs and tissues with the help of mainly 3D printing technology sets as per customer requirement.…”
Section: Additive Manufacturing (Am)mentioning
confidence: 99%
“…It has reported that FFF being performed above the glass transition temperature results in increased adhesion force between the layers; it increases the tendency for better sticking [32]. Also, increasing the bed temperature to a certain limit increases the tensile and flexural strength but started to decrease after crossing this limit due to excessive heat [33]. Table 1 shows the design of the experiment as per the Taguchi L9 orthogonal array.…”
Section: Fff Processmentioning
confidence: 99%